2021
DOI: 10.1002/ajim.23315
|View full text |Cite
|
Sign up to set email alerts
|

Severe visual loss caused by inhalational methanol poisoning in fireworks production: A report on 3 cases

Abstract: BACKGROUNDExplosion injury is a common occupational injury with reworks production. There are few reports about the relationship of severe visual loss and acute methanol poisoning in reworks laborers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, Luo et al [11] reported the successful recovery of visual abilities in three fireworks factory workers who inhaled the methanol. The recovery was possible due to instant diagnosis and treatment that included hemodialysis [11]. The range of possible complications after exposure to methanol is wide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Luo et al [11] reported the successful recovery of visual abilities in three fireworks factory workers who inhaled the methanol. The recovery was possible due to instant diagnosis and treatment that included hemodialysis [11]. The range of possible complications after exposure to methanol is wide.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently no effective treatment methods for this disease due to the multifactorial aspects of eye damage [10]. However, Luo et al [11] reported the successful recovery of visual abilities in three fireworks factory workers who inhaled the methanol. The recovery was possible due to instant diagnosis and treatment that included hemodialysis [11].…”
Section: Introductionmentioning
confidence: 99%